Evaluating the concordance between BICLA and SRI4 in patients with systemic lupus erythematosus from the placebo arms of the EXPLORER and ATHOS trials - Maria Dall’Era; Edward M Vital; Anca D Askanase; Jorge A Ross Terres; Justine Maller; Oliver Meier; Armando Turchetta; Huiyan (Ashley) Mao (Lupus Science and Medicine)
Objective The British Isles Lupus Assessment Group (BILAG)-based Composite Lupus Assessment (BICLA) and the Systemic Lupus Erythematosus Responder Index 4 (SRI4) responses are the most common primary endpoints in SLE clinical trials. We examined the concordance and the reasons for discordance in BICLA/SRI4 responses in participants with SLE receiving placebo and standard of care (SOC) in two randomised controlled trials.Methods This post-hoc analysis included data from the placebo arm (participants treated with SOC) of the EXPLORER (n=87; NCT00137969) and ATHOS (n=80; NCT02908100) trials. Disease activity was measured using BILAG and SELENA-SLEDAI (Safety of Estrogens in Lupus Erythematosus National Assessment-Systemic Lupus Erythematosus Disease Activity Index) in the EXPLORER trial and BILAG-2004 and SLEDAI-2000K in the ATHOS trial. For this analysis, participants were classified as responders or non-responders based on BICLA and SRI4 and the presence of intercurrent events. Concordance and discordance frequencies between BICLA and SRI4 were determined.Results In EXPLORER, the BICLA response rates were lower than the SRI4 response rates (29.9% vs 41.4% at week 52, respectively), whereas in ATHOS the BICLA and SRI4 response rates were similar (41.2% vs 43.8% at week 48, respectively). The overall BICLA/SRI4 concordance (Cohen’s κ score) was moderate (0.46 in EXPLORER and 0.54 in ATHOS at weeks 52 and 48, respectively). At weeks 52 and 48, BICLA+/SRI4− and BICLA−/SRI4+ discordance, respectively, was 6.9% and 18.4% in EXPLORER and 10.0% and 12.5% in ATHOS. In an analysis of ATHOS subgroups based on the presence or absence of rash at baseline, BICLA response was higher at week 48 in participants with arthritis only than in those with arthritis and mucocutaneous comanifestations (63.2% vs 33.9%, respectively). BICLA−/SRI4+ and BICLA+/SRI4− discordance was lower in participants with low compared with normal complement at baseline.Conclusions BICLA and SRI4 may be discordant in SLE trials. Arthritis and rash were the primary drivers of the discordance, and serology influenced BICLA and SRI4 response, suggesting the need for evaluation of multiple efficacy endpoints rather than a single measure.